2008
DOI: 10.1002/jcb.21787
|View full text |Cite
|
Sign up to set email alerts
|

Human beta defensin 2 promotes intestinal wound healing in vitro

Abstract: Limiting microbial threats, maintenance and re-establishment of the mucosal barrier are vital for intestinal homeostasis. Antimicrobial peptides have been recognized as essential defence molecules and decreased expression of these peptides has been attributed to chronic inflammation of the human intestinal mucosa. Recently, pluripotent properties, including stimulation of proliferation and migration have been suggested for a number of antimicrobial peptides. However, it is currently unknown, whether the human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 39 publications
(46 reference statements)
5
54
0
4
Order By: Relevance
“…However, the measured hBD-2 and hBD-3 concentrations from the above-mentioned studies and in our data were low. This prompted us to the assumption that these defensins might preferentially modulate the host immune response by providing an interface between innate and adaptive immune response and promote repair mechanisms in the course of pneumococci pneumonia [9,13,14]. Nevertheless, hBD-2 and hBD-3 might accumulate onto the pulmonary mucosa and display alone or synergistically with other antimicrobial proteins (AMPs) their antimicrobial function in pneumonia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the measured hBD-2 and hBD-3 concentrations from the above-mentioned studies and in our data were low. This prompted us to the assumption that these defensins might preferentially modulate the host immune response by providing an interface between innate and adaptive immune response and promote repair mechanisms in the course of pneumococci pneumonia [9,13,14]. Nevertheless, hBD-2 and hBD-3 might accumulate onto the pulmonary mucosa and display alone or synergistically with other antimicrobial proteins (AMPs) their antimicrobial function in pneumonia.…”
Section: Discussionmentioning
confidence: 98%
“…They modulate cytokine response and selectively chemoattract immune effector cells to the site of inflammation [9]. hBD-2 and hBD-3 promote wound healing by inducing increased cell proliferation [13,14]. Both defensins are expressed in the cells of various mucosal epithelia, including those of the airway [11,12,[15][16][17][18][19].…”
mentioning
confidence: 98%
“…Other investigators have recently shown that HBD2 induces epithelial migration at 1000 ng/ml in the transformed HT29 intestinal cell line (54). In marked contrast, we chose to focus our studies using 20 ng/ml of HBD2, because that concentration is within bactericidal range of the molecule (55) and approximates the concentration of HBD2 observed in human gastric juices and human bronchoalveolar lavage (56).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the mammalian AMPs HBD and LL-37 chemoattract white blood cells and promote epithelial cell migration in wound healing [9,41,43,44]. Hemocytes play critical roles in invertebrate immune and wound-repair systems [45].…”
Section: Discussionmentioning
confidence: 99%